(untitled) (Swiss Medical Weekly, 2015)
The antineutrophil cytoplasmic antibody (ANCA) associated vasculitides (AAV) are a group of primary vasculitides that affect predominantly small- to medium-sized blood vessels. AAV include granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA). Disease severity is dictated by the location and extent of the blood vessels affected. If left untreated, systemic forms of AAV are often fatal. The advent of immunosuppressive therapy (cyclophosphamide plus glucocorticoids) has revolutionised the prognosis for patients with AAV, transforming the course of the disease from fatal to one that can be managed, though not without significant treatment-related toxicity. Recently, the monoclonal antibody rituximab was approved for the treatment of GPA and MPA, providing the first major alternative to cyclophosphamide for induction therapy of AAV. This review explores the emerging role of rituximab in the management of this complex disorder.